PRIMARY SCHOOL TEACHERS’ WELFARE: A PREREQUISITE FOR QUALITATIVE PRIMARY EDUCATION IN NIGERIA - El-Yakub, Shehu Uthman (Sokoto Educational Review, 2015)
Education is the most important vehicle for progress and overall development of individual in particular and society in general. Yearning for positive development and progress cannot come by without sound primary education background, teacher is the prime mover of education in general without whom, education can hardly be acquired. No education system can rise above the quality of its teachers, this gives important support for teacher on their role in the first place, as educators, implementers of the curriculum content and determinant factors that influence the needed learning outcomes of instruction. Primary school teachers in Nigeria suffer serious neglect in terms of their social welfare especially in the areas of salaries and allowances, in-service training, office accommodation as well as inadequate funding of primary education. The paper also brought the issues on child’s needs for education, universal basic education and suggestions were proffered.